66. THE HISTORY OF THE FORMATION OF SPIRITUAL EDUCATION AND EDUCATION OF NEW UZBEKISTAN YOUTH - Mazamkulov Eldor is the son of Makhammadkul (Innovative technologies in construction Scientific Journal, 2023)
This article is based on the issue of spiritual education and upbringing of young people of Uzbekistan from the first formative period to the present day. Today, the dangerous processes taking place on a global scale have a serious impact on all aspects of social life, including the field of education. This leads to various changes in the thinking of young people